Impact of oral conditions on quality of life in peruvian preschoolers in rural and urban areas = Impacto de las alteraciones bucales en la calidad de vida de preescolares peruanos de zonas rurales y urbanas - Peña Alegre, María del Carmen
The objective of this study is to determine the impact of oral conditions on the quality of life related to the oral health of preschool children in a rural and urban area of Cusco. The study was descriptive and cross-sectional, from a population of 179 preschoolers aged 3 to 5 years, from two public early childhood education institutions, and their respective parents or caregivers in the department of Cusco, Peru. We worked with the entire population that met the inclusion and exclusion criteria, seventy-four preschool children were selected for each area, deciding to have the same amount of children per group based on the smallest group. A clinical odonto-stomatological examination was carried out for oral conditions (dental caries, malocclusion, and dental trauma) according to the WHO's criteria and a survey that was used for sociodemographic characteristics. In addition, a validated Peruvian version of the ECOHIS questionnaire was used to obtain data on the impact on quality of life. All the variables of the total and individual scores of the ECOHIS domains were analyzed individually and the Kruskal-Wallis test was used to determine the association between variables. The oral conditions prevalence in preschool children in rural areas referring to dental caries was 100% (dmft index > 6), dental trauma 10.8%, and malocclusions 60.8%; for the urban area dental caries was 93.2% (dmft index > 6), dental trauma 9.5% and malocclusions 36.5%. Of the three oral conditions only the experience of dental caries was related to the OHRQOL of preschoolers in urban and rural areas.